Cost evaluation method for service design based on activity based costing - Kimita, K.; Hara, T.; Shimomura, Y.; Arai, T. (Cranfield University Press, 2009)
As our economy matures, customers have begun to demand more services in addition to just industrial products. To address this problem, designers require a novel engineering methodology, called Service Engineering (SE). SE aims to create value by combining services and products. SE focuses more on increasing customer satisfaction, while general service developers need to take into account economic cost in order to be successful in business. This paper proposes a method to evaluate service from the viewpoints of customer importance and economic cost. The proposed method is verified through its application to a practical case.
Organised by: Cranfield University
Keywords: Product/Service Systems; Design Support; Activity Based Costing